Effects of Bifidobacterium longum BB536 administration on influenza infection, influenza vaccine antibody titer, and cell-mediated immunity in the elderly - Namba, K., Morinaga Milk Industry Co. Ltd., Zama, Kanagawa (Japan). Nutritional Science Lab; Hatano, M; Yaeshima, T; Takase, M; Suzuki, K (Bioscience, biotechnology, and biochemistry, 2010)
Twenty-seven elderly subjects (mean age 86.7±6.6 years) were pre-administered a test food containing 1×10 11 cfu of BB536 daily for 5 weeks (P1), during which they also received influenza vaccination at week 3. The subjects were then randomized to a BB536 group and a placebo group for 14 weeks (P2). The proportion of subjects who contracted influenza was significantly lower in BB536 group than in the to placebo group. The proportion of subjects with fever was also significantly lower in the BB536 group than in the placebo group. In the P1 period, the NK cell activity and the bactericidal activity of the neutrophils were significantly higher at week 5 than to before BB536 administration. In the P2 period, although NK cell activity and neutrophilic activities declined at the end of the study in both the placebo and the BB536 group, neutrophil phagocytic activity and NK cell activity tended to maintain slightly higher levels in the BB536 group than in the placebo group. These results suggest that continuous ingestion of BB536 reduces the incidence of influenza and fever, probably by potentiating innate immunity.